Abundance matching analysis of the emission-line galaxy sample in the extended Baryon Oscillation Spectroscopic Survey. Issue 3 (30th September 2022) - Lin, Sicheng; Tinker, Jeremy L; Blanton, Michael R; Guo, Hong; Raichoor, Anand; Comparat, Johan; Brownstein, Joel R
ABSTRACT: We present the measurements of the small-scale clustering for the emission-line galaxy (ELG) sample from the extended Baryon Oscillation Spectroscopic Survey (eBOSS) in the Sloan Digital Sky Survey IV (SDSS-IV). We use conditional abundance matching method to interpret the clustering measurements from 0.34 to $70\, h^{-1}\, Mpc$ . In order to account for the correlation between properties of ELGs and their environment, we add a secondary connection between star formation rate of ELGs and halo accretion rate. Three parameters are introduced to model the ELG [O ii ] luminosity and to mimic the target selection of eBOSS ELGs. The parameters in our models are optimized using Markov Chain Monte Carlo (MCMC) method. We find that by conditionally matching star formation rate of galaxies and the halo accretion rate, we are able to reproduce the eBOSS ELG small-scale clustering within 1σ error level. Our best-fitting model shows that the eBOSS ELG sample only consists of $\sim 12{{\ \rm per\ cent}}$ of all star-forming galaxies, and the satellite fraction of eBOSS ELG sample is 19.3 per cent. We show that the effect of assembly bias is $\sim 20{{\ \rm per\ cent}}$ on the two-point correlation function and $\sim 5{{\ \rm per\ cent}}$ on the void probability function at scale of $r\sim 20 \, h^{-1}\, \rm Mpc$ .